2007
DOI: 10.1167/iovs.07-0290
|View full text |Cite
|
Sign up to set email alerts
|

Using Pharmacy Claims Data to Study Adherence to Glaucoma Medications: Methodology and Findings of the Glaucoma Adherence and Persistency Study (GAPS)

Abstract: Large pharmacy databases offer insight into medication usage but are vulnerable to errors from sampling (since patients who receive samples will be considered to have poor adherence), misidentification of newly treated patients, and misclassification of added versus switched medications. That a large proportion of patients stop and restart medications makes MPR a robust measure of adherence over time that reflects the resumption of medication after a gap in adherence. The data confirm that adherence to treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
1
8

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(200 citation statements)
references
References 11 publications
5
179
1
8
Order By: Relevance
“…Third, patients prescribed an ocular hypotensive medication o6 months before administration of the questionnaire could not, by definition, report the maintenance behaviour; in our patient groups, only 16% of patients were diagnosed with the condition for which they were receiving ocular hypotensive therapy p1 year previously, further limiting response variability. Fourth, patients who participated in the current research (as well as those included in the survey portion of the Glaucoma Adherence and Persistency Study (GAPS)) 34 may not be representative of the wider population of glaucoma patients as all consented to answer questions about their conditions and medication-taking behaviours. Given these limitations, testing of the instrument in larger, more diverse groups of patients seems warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, patients prescribed an ocular hypotensive medication o6 months before administration of the questionnaire could not, by definition, report the maintenance behaviour; in our patient groups, only 16% of patients were diagnosed with the condition for which they were receiving ocular hypotensive therapy p1 year previously, further limiting response variability. Fourth, patients who participated in the current research (as well as those included in the survey portion of the Glaucoma Adherence and Persistency Study (GAPS)) 34 may not be representative of the wider population of glaucoma patients as all consented to answer questions about their conditions and medication-taking behaviours. Given these limitations, testing of the instrument in larger, more diverse groups of patients seems warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of motivational interviewing has been documented in programmes targeting diet and exercise, 38,39 smoking cessation, 40,41 and medical adherence. 42,43 Although the utility of the current questionnaire and of motivational interviewing in patients prescribed ocular hypotensive therapy requires further testing, others 19,32,34,[44][45][46][47][48][49] have found adherence in this patient population to be problematic and have identified several barriers that parallel the situational issues (eg, forgetting when travelling or when the regular schedule changed 19 ) reported broadly by patients in both the glaucoma and multispecialty practices. Research is needed to further specify health-related beliefs, lapses in or dissatisfaction with doctor-patient communication, and situational obstacles that negatively impact adherence in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…[23,24] This definition was been completed as "the extent to which a patient participates in a treatment regimen after he or she agrees to that regimen. " [25,26] In publication several methods are reported to calculate the adherence to treatment such as Continuous Measure of Medication Acquisition (CMA) [27][28][29]; Medication Possession Ratio (MPR) [30][31][32][33]; Medication Refill Adherence (MRA) [34][35][36]; Proportion of Days Covered (PDC) [37][38][39]; Refill Compliance Rate (RCR) [40][41][42]; Medication Possession Ratio, modified (MPRm) [43][44][45] [46]; and Received Daily Dose/Prescribed Daily Dose [47]. Only the last method consider the Prescribed Dose and not the Defined Dose, approaching most of all to the WHO definition, that take in consideration the treatment regimen prescribed by physician.…”
Section: Medication Adherencementioning
confidence: 99%
“…With COAG patients, the probability of remaining persistent with topical prostanoids over the first year of therapy is typically less than 60%; this is despite the encouraging overall patient persistence with topical prostanoids compared with all other classes of topical ocular hypotensives [5][6][7][8][9][10][11][12][13][14] . Interestingly, it has been reported that patient persistence with prostaglandin analogues is even inferior to that of other chronic therapies, including those for management of hyperlipidaemia (statins), osteoporosis (bisphosphonates), and type II diabetes (oral hypoglycaemic agents) 15 .…”
Section: I a L D I S T R I B U T I O N U N A U T H O R I Z E D U S mentioning
confidence: 99%